The Clinical Significance and Prognostic Value of HER2 Expression in Bladder Cancer: A Meta-Analysis and a Bioinformatic Analysis - Gan, Kai; Gao, Yue; Liu, Kuangzheng; Xu, Bin; Qin, Weijun (Frontiers in Oncology, 2021)
Abstract Objective: Human Epidermal Growth Factor Receptor 2 (HER2) is highly expressed in multiple malignancies and associated with patients’ prognosis, but its role in bladder cancer (BCa) remains elusive. We conducted this meta-analysis to explore the clinical significance and prognostic value of HER2 in BCa. Methods: PubMed was searched for studies published between January 1, 2000 and January 1, 2020. The odds ratios (ORs) and hazard ratios (HRs) with 95% confidence intervals (95%CIs) were used to investigate the relationship between HER2 and BCa pathological features. TCGA was mined for the information regarding as well. Results: Our study included 14 articles enrolling 1398 people. Expression of HER2 is higher in bladder cancer than in normal tissues. HER2 over-expression is associated with CIS, multifocal tumor, large tumor size, high tumor stage and grade, lymph node metastasis, progression, recurrence and papillary tumor. We could not find a significant association between HER2 expression and survival time in BCa patients. Conclusions: Our meta and bioinformatic analysis indicated that HER2 expression was related to pathological malignancy and poor prognosis in BCa.